Heuristic Coupling Design-Optimization between a Variable Speed Generator and a Wind Rotor - Cherif Khelifi; Ferroudji, Fateh; Meguellati, Farouk; Koussa, Khaled (International Journal of Engineering Research in Africa, 2017)
A high emergence of wind energy into the electricity market needs a parallel efficient advance of wind power forecasting models. Determining optimal specific speed and drive-train ratio is crucial to describe, comprehend and optimize the coupling design between a wind turbine-rotor and an electric generator (EG) to capture maximum output power from the wind. The selection of the specific design speed to drive a generator is limited. It varies from (1-4) for vertical axis wind turbines and (6-8) for horizontal axis wind turbines. Typically, the solution is an iterative procedure, for selecting the adequate multiplier ratio giving the output power curve. The latter must be relatively appreciated to inlet and nominal rated wind speeds. However, instead of this tedious and costly method, in the present paper we are developing a novel heuristic coupling approach, which is economical, easy to describe and applicable for all types of variable speed wind turbines (VSWTs). The principle method is based on the fact that the mechanical power needed of the wind turbine (WT) to drive the EG must be permanently closer to the maximum mechanical power generated by the (WT).